3m-2(4m+5)=10+5m

Simple and best practice solution for 3m-2(4m+5)=10+5m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3m-2(4m+5)=10+5m equation:



3m-2(4m+5)=10+5m
We move all terms to the left:
3m-2(4m+5)-(10+5m)=0
We add all the numbers together, and all the variables
3m-2(4m+5)-(5m+10)=0
We multiply parentheses
3m-8m-(5m+10)-10=0
We get rid of parentheses
3m-8m-5m-10-10=0
We add all the numbers together, and all the variables
-10m-20=0
We move all terms containing m to the left, all other terms to the right
-10m=20
m=20/-10
m=-2

See similar equations:

| 5x+(−11)=34 | | .5y−8=−10 | | 2x+14=x+32 | | 42=17x+8 | | 20-1/22(2x)=101/22(x) | | -22+10(p+10)=4-5(2p+11) | | 2x+14=x+40 | | 5p−2p=9 | | 5x+13=2x-26 | | |10+5b|=10 | | 2x-4(x-3)=-2+3×-6 | | 36-7x=7x(x-5) | | 9x+13=x+65 | | 5^3x-30=27 | | 5+y=43 | | 4(-x+1)=4(1-x) | | 1092y+2)-y=2(8y-8) | | 41=9r-4 | | 4(-x+1)=4(1-x | | 7x+13=x+94 | | -6-24=5x | | 9/5c=82 | | 4a+7+2a=11 | | r-6=-3 | | -17x+8+x=24 | | 1x/3-5=-8 | | e-6=-3 | | (1/2)^x=1/16 | | F(x)=36-8 | | -4(x+4)=16x-64 | | 17x+8=175 | | (1/3a)=7 |

Equations solver categories